The Influence of Job Training, Teamwork, and Competence on Employee Career Development - Yanthy Herawaty Purnama; Fathihani; Setiyo Purwanto (Dinasti Publisher, 2023)
This study aims to determine the Effect of Job Training, Teamwork and Competence on Employee Career Development. This research was conducted at a company engaged in the service sector, namely the delivery of export and import cargo located in Tangerang City. In practice, employee career development is still based on seniority and employees who have worked longer to be promoted to their position level. Regardless of the training, ability to work together and competence of these employees. Respondents in this study amounted to 75 employees as the respondent. The sampling technique used purposive random sampling, and the analysis technique used Structural Equation Modeling (SEM) with a questionnaire as the research instrument.